EDUKASI GIZI MENGGUNAKAN KALENDER EDUKASI STUNTING (KALSITING) MENINGKATKAN PENGETAHUAN IBU BALITA UNTUK PENCEGAHAN STUNTING - Rahmat, Mamat; Isdiany, Nitta (Media Penelitian dan Pengembangan Kesehatan, 2024)
The stunting prevalence stunting in Cimahi as a result of the 2022 Indonesian Nutrition Status Survey  was 16.4. The prevalence of stunting is expected to 14% by 2024. The education level  and nutritional knowledge of toddler mothers is significantly related to the incidence of stunting. However, the education level and nutritional knowledge of toddler mothers in Cimahi are still low. Therefore, nutrition education is needed to increase the knowledge of toddler mothers regarding stunting. The study aimed to determine the influence of nutrition education using the stunting prevention education calendar (kalsiting) on the knowledge of toddler mothers for stunting prevention. This study used quasi experiment design, two groups with control group. The research location in Pasirkaliki Village, Kota Cimahi, West Java. The research sample was 30 mothers who had children aged 0-59 months. Statistical analysis used the Willcoxon test, independent t-test, Paired t-test, Mann Whitney U test. The results showed that the average score of knowledge increase in the treatment group was higher than that of the control group (p=0.031<0.05), there was a significant difference in the average increase in knowledge between the treatment group and the control group. However, there was no difference in the average increase in Z-Score height by age (HAZ)and weight by age (WAZ) before and after three months of nutrition education using leaflet media (p>0.05). Providing nutrition education using the media of the stunting prevention nutrition education calendar (Kalsiting) and by using leaflet media has been proven to significantly increase maternal nutrition knowledge.